Peran UMKM (Usaha Mikro, Kecil, Dan Menengah) Dalam Meningkatkan Pembangunan Ekonomi Di Indonesia - Putri Salsabila Indrawan Lubis; Rofila Salsabila (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
There are various classes for firms in Indonesia, according legal rules. Businesses can be classified into four categories: enormous, micro, small, and medium. The government refers to the three primary categories of businesses as UMKM, or micro, small, and medium enterprises. For this reason, "Micro, Small, and Medium Enterprises" is what the abbreviation UMKM stands for. MSMEs are governed under Law No. 20/2008 on "Micro, Small, and Medium Enterprises". The existence of MSMEs makes it easier for people across Indonesia to fulfill these needs. MSMEs play an important role in encouraging employment, economic growth, and reducing social inequality. In addition, MSMEs are essential to solving a number of challenges facing the nation's economy. MSMEs still face various obstacles and constraints in carrying out this task, so they cannot realize their full potential and contribution in social and economic activities. The community, the banking sector as a source of credit, and the government as a policy maker must fully participate in finding solutions.